FRI0538 Development and Validation of a Questionnaire for the Identification of Different Behavioral Strategies in Patients with Chronic Low Back Pain. (9th June 2015) - Bailly, F.; Foltz, V.; Rozenberg, S.; Gossec, L.; Fautrel, B.
Abstract : Background: Patients with low back pain (LBP) have to manage their symptoms, and different behavioral strategies (BS) can alter the impact of LBP. IBS identification is an important challenge to optimize the care of LBP patients. Objectives: To elaborate and validate a questionnaire identifying BS in patients with LBP. Methods: (1) Qualitative study of 25 patients with LBP by 4 focus groups and identification of major behaviours. (2) Construction of a preliminary questionnaire with multiple items, based on experts' opinions and the verbatim of patients, representing 3 to 4 different behavioral strategies. (3) Validation of the questionnaire through a prospective multicentric study in France and Switzerland, including patients with chronic LBP. Demographic characteristics, the preliminary questionnaire and other reference anchor questionnaires were collected. Multiple component analysis and hierarchical classification were used to validate the existence of different behavioral strategies and to reduce the number of items. Construct validity, internal consistency (Cronbach's alpha) and external validity were evaluated. (4) Longitudinal validation: therapeutics performed during 12 month of follow up were collected. Results: (1 and 2) The preliminary questionnaire was composed of 85 items in 8 different domains. (3) In the validation study, 162 patients were included: 42% were men and the median age was 50 years (range, 22 to 82). Multiple component analysis found 3 different behavioral profiles: (a) patients who need physical reassurance, (b) patients who need psychological support, and (c) patients who manage their daily activities adequately. The final questionnaire is composed of 7 questions, each question deals with a different domain of coping (e.g., work or leisure activities) and each question is answered by choosing one of 3 items, corresponding to the 3 different behavior strategies. The predominant BS is determined by the BS getting the most answers. Cronbach's alpha was moderate (range, 0.47-0.66). External validity assessed against anxiety, depression, and coping strategies was satisfactory. (4) As expected, over 12 months in 85 patients, intensive back pain therapy was more often conducted in patients who needed physical reassurance (p=0.038). Conclusions: This short and easy to use questionnaire distinguishes 3 profiles of BS in LBP and appears to have good validity. This questionnaire should be useful in managing patients as patients with profile (a) may most benefit from intensive physical therapy whereas patients with profile (b) should be oriented towards psychological support and/or medications. Disclosure of Interest: None declared